Can Thinking be Taught? Linking Critical Thinking and Writing in an EFL Context. (April 2015) - Mehta, Sandhya Rao; Al-Mahrooqi, Rahma
While thinking critically is often perceived to be the primary purpose of reading, the question of whether it can actually be taught in classrooms has been extensively debated. This paper bases itself on a qualitative case study of university students completing a degree in English Language and Literature. It explores the way in which critical thinking can be taught in EFL contexts. The paper suggests that critical thinking is best defined as a series of skills which can be continuously worked upon by students for whom constant revision and application of these skills is a significant way of internalizing what has often been seen to be just an attitude or bent of mind. This skill is further enhanced when students get an opportunity to write on the areas which have been discussed in the class, particularly if they are of some relevance to the students' own contexts. Based on the open question format of Norris and Ennis (1989) and subsequent evaluation using the rubrics of McLaughlin and Moore (2012) which take into account the critical reading component in writing, this paper investigates the extent to which critical thinking could be enhanced through in-class social practices such as discussions and subsequent writing. The study concludes that continuous practice, both oral and written, provide opportunities for students to develop their critical thinking abilities as they become more successful in incorporating nuanced and critical ideas into their academic writings. This has implications for students' academic and personal achievements because, clearly, an inability to read critically will result in an inability to write insightfully. Various strategies are then suggested to facilitate learners' use of critical thinking skills so that they may successfully incorporate them into their writing, both in an academic context and as a life-long skill.